Odpowiedź :
Odpowiedź:
a)
(10x - 5y + 1) : 5 = 2x - y + 1/5
b)
(2a - 6ab)/2 = a - 3ab
c)
(12p - 9r - 2) : 3 = 4p - 3r - 2/3
d)
(4g - 8h + 1)/2 = 2g - 4h + 1/2
e)
(3m + 6) : 6 = 1/2m + 1
f)
(8t - 4s)/4 = 2t - s
Szczegółowe wyjaśnienie:
Odpowiedź:
a)
[tex](10x-5y+1):5=2x-y+\frac{1}{5}[/tex]
b)
[tex]\frac{2a-6ab}{2} =\frac{2}{2} a-\frac{6}{2} ab=a-3ab[/tex]
c)
[tex](12p-9r-2):3=4p-3r-\frac{2}{3}[/tex]
d)
[tex]\frac{4g-8h+1}{2} =\frac{4}{2}g -\frac{8}{2}h +\frac{1}{2} =\\ =2g-4h+\frac{1}{2}[/tex]
e)
[tex](3m+6):6=\frac{3}{6}m +\frac{6}{6} =\frac{1}{2} m+1[/tex]
f)
[tex]\frac{8t-4s}{4} =\frac{8}{4} t-\frac{4}{4} s=2t-s[/tex]